2021
DOI: 10.1111/ggi.14168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hypertonic dehydration among older patients admitted to the emergency department: A prospective cross‐sectional study

Abstract: The prevalence of hypertonic dehydration (HD) among community-dwelling and hospitalized populations has been evaluated. However, to our knowledge, no study had previously focused on older patients admitted to the emergency department (ED). The present study aimed to evaluate the prevalence, risk factors and short-term outcomes of HD among Thai older patients admitted to the ED.Methods: This was a prospective cross-sectional study at one urban ED in Thailand. Patients aged ≥65 years who were admitted to the ED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The model fit was tested using the Hosmer-Lemeshow goodness-of-fit , which showed a value of 0.93. The covariate potential associated with HD included age, gender, BMI [20], daily water intake, 6-CIT score (cognitive function) [10], mini nutrition assessment score [20], activities of a daily living score, CCI [9, 14], hypertension, number of medications used, the medication used [10], history of falls, and the quality of mobility by using the Stopping Elderly Accidents, Death & Injuries (STEADI) question [21]. The risk score was developed based on the final multiple logistic regression model and internal validation using the method described by Sullivan et al [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model fit was tested using the Hosmer-Lemeshow goodness-of-fit , which showed a value of 0.93. The covariate potential associated with HD included age, gender, BMI [20], daily water intake, 6-CIT score (cognitive function) [10], mini nutrition assessment score [20], activities of a daily living score, CCI [9, 14], hypertension, number of medications used, the medication used [10], history of falls, and the quality of mobility by using the Stopping Elderly Accidents, Death & Injuries (STEADI) question [21]. The risk score was developed based on the final multiple logistic regression model and internal validation using the method described by Sullivan et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review among older adult nursing home residents indicated that the prevalence of HD varied between 0.8 and 38.5% using a variety of different methods [13]. One study of Thai older adults who visited the emergency department found that 21.1% presented with HD, and that a Charlson comorbidity index (CCI) score ≥5 was associated with HD [14]. Increased age, underlying diabetes mellitus (DM), and cognitive impairment had found to be a risk for impending HD in the UK hospital [10].…”
Section: Introductionmentioning
confidence: 99%
“…Buaprasert et al according to a study in patients with emergency admission 1/5 of the existence of high permeability dehydration. 6 Previous experiments have shown that in the state of hypertonic dehydration, the blood volume is relatively reduced, the blood is concentrated, and the blood viscosity is increased, which can not meet the blood supply of the corresponding organs. This is one of the important reasons leading to preoperative hypoperfusion of blood volume in patients with A AAD.…”
Section: Introductionmentioning
confidence: 99%